Malaysian accounting educators’ perceptions on ethics education in the accounting curriculum - Win, Yin Yin; Ismail, Suhaiza; Abdul Hamid, Fatima (Accounting Research Institute, 2014)
Purpose: This study aims to investigate ethics education in the accounting curricula of public universities in Malaysia based on the perception of the educators. Specifically, the study explores preparedness of educators in teaching ethics, preferred methods of ethics instruction, and educators’ perceptions of the importance of ethics integration. Design/methodology/approach: A questionnaire survey was distributed to 370 accounting educators in various public universities in Malaysia. The data were analyzed using the Statistical Package for the Social Sciences (SPSS) software. Basically, rudimentary statistical analysis techniques of frequency, percentage and central tendency were used to answer the research questions. Findings: The findings revealed that accounting educators agree on the importance of ethics education to satisfy the profession’s needs. However, different opinions exist among educators on the adequacy of ethics education scope. Originality/value: The present study is one of the few studies that explore the current status of ethics integration in the accounting curriculum or the perception of accounting educators on this issue particularly from a developing country perspective.